Evaluating sweetpotato clones for consumers in southwestern Nigeria - Edebiri, O.; Egeonu, I.; Akoroda, M.O. (2004)
Sweetness, consistency, fibre content and yield are good criteria determining consumer's preference of boiled sweet potato (Ipomoea batatas L.) roots in the south-western Nigeria. From July 2000 to September 2001, some 15 sweet potato clones were evaluated at Ibadan so as to recommend suitable ones for cultivation and consumption in this area. Three trials was carried out within this period in the field, polybag and then field environments. The mean fresh root yield for all trialsacross 3,4 and 5 months after planting range from 1.57 to 12.66, 5.81 to 29.96 and 14.18 to 48.10t/ha respectively. Dry matter yield of root ranged from 0.56 to 4.67, 2.04 to 11.58 and 3.81 to 18.37t/ha respectively in the same harvest periods.